2001
DOI: 10.1046/j.1432-1327.2001.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of key residues identifies the connection subdomain of HIV‐1 reverse transcriptase as the site of inhibition by heme

Abstract: We have recently demonstrated that metalloporphyrins are potent inhibitors of both human immunodeficiency virus type 1 (HIV-1) and human immunodeficiency virus type 2 (HIV-2) reverse transcriptases (RTs) [Argyris, E.G., Vanderkooi, J.M., Venkateswaran, P.S., Kay, B.K., and Paterson, Y. (1999) J. Biol. Chem. 274, 1549-1556]. In addition, by screening a phage peptide library we discovered that a peptide with sequence similarity to residues 398-407 from the connection subdomain of HIV RTs binds heme. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Hence, the tetrapyrrole and naphthylurea derivatives may have similar inhibition mechanisms. Notably, like KM-1 hemin derivatives also block HIV-1 RT, supposedly by stacking interactions between the porphine ring and aromatic residues in the protein (1). Similar interactions may occur with the aromatic ring systems in the carbonyl J acid compounds.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, the tetrapyrrole and naphthylurea derivatives may have similar inhibition mechanisms. Notably, like KM-1 hemin derivatives also block HIV-1 RT, supposedly by stacking interactions between the porphine ring and aromatic residues in the protein (1). Similar interactions may occur with the aromatic ring systems in the carbonyl J acid compounds.…”
Section: Discussionmentioning
confidence: 95%
“…It has been previously reported that hemin could also inhibit human immunodeficiency virus (HIV) RT (2) by potentially binding to residues 398 to 407 within the connection domain of HIV RT. Further mutagenesis studies showed that the tryptophan residues at positions 401 and 402 were important for hemin binding to the HIV RT (1). Future studies will be required to define the exact hemin binding site(s) in the hepadnavirus TP and RT domains.…”
Section: Discussionmentioning
confidence: 99%
“…A cationic phthalocyanine was reported to inhibit human rhinovirus type 5 (RV-5) infection [21]. Selected porphyrin derivatives inhibit specific viral targets including retroviral reverse transcriptase [22-26] and HIV-1 protease [27]. …”
Section: Discussionmentioning
confidence: 99%